Cinévardaphoto - Varda, Agnès; Csongova, Per Olaf; Duguet, Claire; Escoffier, Jean-Yves; Holosko, John; Kearney, Rick; Marques, J.; Rabaud, Pascal; Seitz, Markus (Cinema Guild, 2010)
From Agnes Varda, director of "The Beaches of Agnes" and "The Gleaners and I", comes the wonderful "Cinevardaphoto", a triptych of short films exploring the power and vitality of the photograph. In "Ydessa, the Bears and etc.", Varda discovers a haunting exhibit of found photos, each incorporating a teddy bear. With "Ulysses", she deconstructs a picture from her early career as a photographer. While the exuberant "Salut les Cubains" uses still photos to capture the spirit of the Cuban revolution's early days. [Cover]